Peculiarities of THz-electromagnetic wave transmission through the GaN films under conditions of cyclotron and optical phonon transit-time resonances - Korotyeyev, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
The theory of THz radiation transmission through the film of compensated
GaN of cubic modification under action of electric and magnetic fields has been
developed. In the THz frequency range, spectra of the dynamic mobility tensor have been
obtained for applied steady-state electric fields of several kV/cm and magnetic fields of
several T. The spectra of transmission, reflection and loss coefficients have been
analyzed for the Voigt configuration used for the applied fields. It has been shown that
the transmitted wave becomes elliptically polarized, and the spectra of polarization
characteristics such as ellipticity and rotation angle of the large axis of polarization
ellipse were investigated under conditions of cyclotron resonance and optical phonon
transit-time one. It has been found that, in certain frequency bands, polarization
characteristics have the features valid for both resonances. The new optical method based
on the analysis of ellipticity and rotation angle spectra is offered for determination of the
low-field mobility.